SISTEM KONTROL OTOMATIS KONDISI AIR PADA BUDIDAYA IKAN GUPPY BERBASIS IOT - M. Rivalullah Zaelani; Muhammad Purnama; Aan Febriansyah; Irwan Irwan (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Guppies are one type of ornamental fish that are usually kept in aquariums. Water quality is an important factor for the success of this fish culture, such as pH value, temperature, and water level. Then a control system was made that can stabilize the temperature and pH of the water in the aquarium which aims to facilitate IoT-based guppy fish cultivation. Sensors used to read values ​​in water conditions are pH 1402C sensor, DS18B20 sensor, and HCsr-04 ultrasonic sensor. The average percentage error of the pH sensor test data is 0.456%. The average error percentage from the temperature sensor test data is 0.126%. The average error percentage of the ultrasonic sensor test data is 0.278%. The system on temperature control if the aquarium temperature is below 23°C then the heater will turn on, if the aquarium temperature is above 27°C then the fan is on and if the temperature is around 23°C - 27°C then the heater and fan will turn off. In the pH control system there are two push buttons to increase and decrease the pH value in the aquarium.